Restructuring Port Governance in South Africa - Ayanda Meyiwa; Mihalis Chasomeris (Journal of Economic and Financial Sciences, 2016)
South Africa’s (SA) ports do not have a clearly defined port doctrine. They have certain elements resembling the Anglo-Saxon port doctrine, others the Continental doctrine and still others the Asian port doctrine. Thus, SA encounters conflicting port objectives: it runs a complementary ports system where costs are not reflective of prices charged, and the revenues and costs allocated to various commodity types remain unjustified. This is against the backdrop of intra-port, inter-port and multimodal cross-subsidisation, which found justification in SA’s developmental objectives but has been viewed as unjustifiable under current economic conditions, giving rise to dissatisfaction among various port stakeholders regarding Transnet as a state-owned enterprise and Transnet National Ports Authority’s (TNPA) governance and pricing practices that have not been adequately addressed. Using content analysis, 18 stakeholders’ submissions on the 2013-2014 TNPA tariff application, 15 stakeholders’ submissions regarding the multi-year tariff application, and 16 submissions regarding the 2014-2015 tariff application were assessed. The focus was on finding links between challenges faced by stakeholders and whether solutions would be found through SA adopting a different port doctrine. The findings show that while the Asian doctrine is more aligned with SA’s developmental objectives, adoption of it may prove premature in view of the current and foreseeable economic conditions. The study shows that the local port system may not find a perfect fit into any of the known port models and established port doctrines, but, instead, that SA needs to articulate its own port doctrine.